The Construction of Tarbiyyah Ruhiyyah in Asasu al-Tarbiyatu al-Islamiyatu fi al-Sunnati al-Nabawiyati by Abdul Hamid al-Sayyib al-Zintani: A Discourse Analysis of a Religious Text - Hasan Basri; Andewi Suhartini; Asep Nursobah; Siti Nuraeni Muhtar (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2026)
This article examines the construction of Tarbiyyah Ruhiyyah in Asasu al-Tarbiyatu al-Islamiyatu fi al-Sunnati al-Nabawiyati by Abdul Hamid al-Sayyib al-Zintani within the fields of religious literature and Islamic educational thought. While recent scholarship has addressed spirituality, Islamic education, and character formation, limited attention has been given to how Tarbiyyah Ruhiyyah is discursively constructed within a religious book as a textual object of analysis. This study aims to analyze the textual construction of Tarbiyyah Ruhiyyah, identify its main discursive elements, and explain the relationships among religion, faith, fitrah, morality, and personality formation. Using a qualitative design and discourse analysis, the study focuses on the chapter on spiritual education, treating definitional passages, Qur'anic verses, hadith citations, and normative arguments as its primary units of analysis. The study finds that Tarbiyyah Ruhiyyah is constructed as a core component of integrated Islamic education, grounded in a theology of human nature derived from Islamic revelation that links innate religiosity, faith, morality, and holistic human development, and that its authority is rooted in the Sunnah and operationalized through Prophetic methods including exemplarity, worship habituation, gentleness, environmental guidance, and gradual instruction directed toward forming a balanced human personality. The article contributes to religious literature studies by demonstrating that an Islamic educational text can be analyzed as a religiously authorized discourse in which spiritual formation is constructed through definitional strategies, scriptural sequencing, and moral argumentation.